Work Arrangement Dynamics and Work–Life Experiences among Online Resellers - Susana M. W. Mustika; Charliany Hetharia (Journal of Management and Business Innovation, 2026)
This study examines the dynamics of work arrangements and work–life experiences among online resellers in Sorong City, focusing on how flexible work practices shape the management of work and personal life in an informal digital economy context. A quantitative survey was conducted involving online resellers operating through social media platforms. Data were analyzed using descriptive statistics and simple linear regression to explore associations between work arrangement practices and work–life experiences. This study extends work–life balance and flexible work literature by providing empirical evidence from informal digital work in Eastern Indonesia, highlighting flexibility as both autonomy and responsibility. Findings inform policymakers and development programs to design digital entrepreneurship initiatives that integrate economic support with worker well-being considerations. The study is limited by its cross-sectional design and single-city focus. Future research should adopt longitudinal and comparative approaches.